Correlation Study of Landfill Leachate Concentration and Resistivity Value for Prediction of Landfill Leachate in Shallow Groundwater - Kamarulzaman M.N.; Zawawi M.H.; Ahmad A.; Mazlan M.A.; Hassan N.H.; Kamaruddin M.A. (Springer Science and Business Media Deutschland GmbH, 2025)
Electrical resistivity imaging (ERI) is being applied to hydrogeological applications studies like survey of groundwater contamination. Monitoring of groundwater using this approach was more effective because it does not use wells for observation. Among the purposes of this research were to determine the leachate and sand characteristics, evaluate the resistivity for different types of permeating fluids and measure the resistivity correlation between water and leachate. Due to the infiltration of leachate, the bad impact at the landfill site has been declared will give contribution to groundwater contamination. Methods that have been implemented was soil box method. The purpose of this method is to measure the electrical resistivity of permeates liquid and sand sample. The moist fine sand was placed into an oven of 100C for 24h to obtain the dried fine sand oven. Various materials have been tested such as leachate, tap water, and distilled water for 15, 30, and 45ml with dried fine sand oven. Characteristics of leachates were determined from dissolved solid determination, turbidity measurement, colour measurement, and more. It can be summarized that the resistivity value of leachate is lower than that of tap water and distilled water. Also, from the comparison it can be concluded that leachate gives minimal impact for turbidity value as soil itself has a great effect on increasing the value of turbidity. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.